2018
DOI: 10.1108/edi-11-2016-0105
|View full text |Cite
|
Sign up to set email alerts
|

Justice and fairness in the workplace: a trajectory for managing diversity

Abstract: Purpose The purpose of this paper is to argue that diversity management (DM) interventions, underpinned by principles of justice and fairness, create a powerful force that drives sustainable outcomes. Further, the authors argue that justice and fairness should be embedded at the core of DM. Design/methodology/approach A qualitative case study methodology was used to ascertain how four organizations approached critical issues regarding diversity. Justice and fairness principles were used as a framework to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 75 publications
0
20
0
1
Order By: Relevance
“…Thus, more people would have access to achieve justice. In this sense, Dahanayake and colleagues [40] emphasize the discrimination in the very different contexts in which the second order of sexual harassment may occur, highlighting the importance of integrating justice and fairness standards when implementing programs of diversity management, arguing that social justice provides benefits for society. In this way, more people will be encouraged to intervene, both in case of witnessing a case of direct violence and SOSH violence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more people would have access to achieve justice. In this sense, Dahanayake and colleagues [40] emphasize the discrimination in the very different contexts in which the second order of sexual harassment may occur, highlighting the importance of integrating justice and fairness standards when implementing programs of diversity management, arguing that social justice provides benefits for society. In this way, more people will be encouraged to intervene, both in case of witnessing a case of direct violence and SOSH violence.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel studies had suggested that a relationship between the two variables might exist ( Roberson and Stevens, 2006 ; Brooke and Tyler, 2010 ; Fujimoto, 2013 ; Kulik and Yiqiong, 2015 ; Dahanayake et al, 2018 ). Roberson and Stevens (2006) found a relationship between justice perceptions and equality incidents; specifically, that equality incidents that had been viewed as negative were more likely to cite justice issues.…”
Section: Conceptualising Organisational Justicementioning
confidence: 99%
“…Stone-Romero and Stone (2005) theorized that employee perceptions of justice underpinned employee response to equality approaches, proposing that a perceived absence of justice would result in deviant behaviours toward the out-group such as harassment and discrimination. A relationship between the two variables, employee attitudes toward company equality approaches and perceptions of interactional justice is implied but lacking in empirical evidence (see also Roberson and Stevens, 2006 ; Brooke and Tyler, 2010 ; Fujimoto, 2013 ; Kulik and Yiqiong, 2015 ; Dahanayake et al, 2018 ).…”
Section: Conceptualising Organisational Justicementioning
confidence: 99%
“…Distributional justice is based on Adams' (1965) equity theory (Choi, et al, 2013;Mao, et al, 2016) and concerns the perceived justice for the allocation of resources by the organization and the distribution of outputs (Ribeiro, & Semedo, 2014). Procedural justice is the fairness of the processes related to the outputs, i.e, the extent to which employees perceive the rules and procedures in this process (Dahanayake, et al, 2018). Therefore, while distributional justice is justice perception related to output, procedural justice is concerned with the processes of distributing outputs, not outputs.…”
Section: Interactional Justicementioning
confidence: 99%